On Some Properties of Solutions of Second Order Rational Recursive Sequences - Zienab A. Elmaned (مجلة البيان العلمية, 2023)
Equations that enable us to iteratively calculate a function’s value from a given set of values are commonly the foundation of mathematical computations. Such as equations are known as recurrence equations or a difference equation. In this paper, we study some known properties of this kind of equations. Some new results are provided which are consistent with several results from earlier researches that deal with second order recursive rational difference equations